Experimental and Simulative Investigation of Laser Transmission Welding under Consideration of Scattering - Devrient, M.; Da, X.; Frick, T.; Schmidt, Michael (Physics Procedia, 2012)
Laser transmission welding is a well known joining technology for thermoplastics. Because of the needs of lightweight, cost effective and green production thermoplastics are usually filled with glass fibers. These lead to higher absorption and more scattering within the upper joining partner with a negative influence on the welding process. Here an experimental method for the characterization of the scattering behavior of semi crystalline thermoplastics filled with short glass fibers and a finite element model of the welding process capable to consider scattering as well as an analytical model are introduced. The experimental data is used for the numerical and analytical investigation of laser transmission welding under consideration of scattering. The scattering effects of several thermoplastics onto the calculated temperature fields as well as weld seam geometries are quantified.
Created from Fastlane, Scopus look-up
Keywords: finite element model; laser transmission welding; process simulation; scattering; thermoplastics